Origin of the vertebral artery examined with CTA - Dodevski, Ace; Zhivadinovikj Bogdanovska, Julija; Papazova, Marija; Lazareska, Menka; Stojovska Jovanovska, Elizabeta; Jakimovska Dimitrovska, Maja; Kostov, Milenko (Czech Anatomical Society, 2021)
The vertebral artery and its branches are target of arteriographic investigations, ultrasound and Doppler visualization, MRI and CT imaging in many contemporary diagnostic procedures. The aim of this study was to examine vertebral artery origin, as well as its variations, and to emphasize their clinical importance. We examined radiographs of patients who had CT angiography undertaken for a variety of clinical reasons, performed as a part of their medical treatment at the University Clinic for Radiology in Skopje, R. Macedonia. The study population included 103 patients, 58 males and 45 females, age range from 25-82, mean age 58.4 years. The left vertebral artery arose from the left subclavian artery in 94.17% and the right vertebral artery had origin from the right subclavian artery in 99.02%. Variable origin of the left vertebral artery from the aortic arch was noticed in 5.82% of the patients. In one patient (0.97%) we found atypical arisen of the right vertebral artery from the right common carotid artery in combination with an aberrant right subclavian artery. Although anatomically interesting, an awareness of the vertebral artery anatomy and variations is clinically important. A precise understanding of the vertebral artery anatomy is fundamental for planning and performing endovascular procedures and neuro-interventions, as well as for the accurate interpretation of ischemic areas. For the anatomists, the results obtained from this study present valuable teaching material for students and postgraduates.
Keywords: vertebral artery; anatomy; variations